2018
DOI: 10.1002/hed.25064
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter assessment of exclusive endoscopic endonasal approach for the treatment of 53 olfactory neuroblastomas

Abstract: Exclusively endoscopic treatment proved efficient and reliable in a large controlled series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 30 publications
3
24
0
Order By: Relevance
“…After title and abstract review, 350 articles were rejected and full-texts of the remaining 66 papers were obtained for further review. After applying the aforementioned eligibility criteria, a total of 9 studies were included in the qualitative and quantitative synthesis (22)(23)(24)(25)(26)(27)(28)(29)(30) . The reasons behind the exclusions of the other studies are shown in Figure 1.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…After title and abstract review, 350 articles were rejected and full-texts of the remaining 66 papers were obtained for further review. After applying the aforementioned eligibility criteria, a total of 9 studies were included in the qualitative and quantitative synthesis (22)(23)(24)(25)(26)(27)(28)(29)(30) . The reasons behind the exclusions of the other studies are shown in Figure 1.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…6,7,10,19-30 Of the articles that did not include IPD, 15 corresponding authors were contacted to provide raw data for their studies. 3,31-45 Six authors responded, and 5 provided IPD. 33,34,37,40,41,43 Nine corresponding authors did not respond after 2 inquires.…”
Section: Resultsmentioning
confidence: 99%
“…Following the adoption of this technique for the resection of pituitary tumors, it was adapted for resection of extrasellar skull base lesions (6)(7)(8)(9). Fully endoscopic approaches are now in widespread use in the management of malignancies of the ventral skull base, including esthesioneuroblastoma, chordoma, and chondrosarcoma, as well as aggressive, locally invasive pathologies such as meningiomas, and craniopharyngiomas (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%